2005
DOI: 10.1111/j.2006.0906-7590.04372.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of landscape composition and substrate availability on saproxylic beetles in boreal forests: a study using experimental logs for monitoring assemblages

Abstract: K. 2006. Effects of landscape composition and substrate availability on saproxylic beetles in boreal forests: a study using experimental logs for monitoring assemblages. Á/ Ecography 29: 191 Á/204.Intensive forestry practises in the Swedish landscape have led to the loss and fragmentation of stable old-growth habitats. We investigated relationships between landscape composition at multiple scales and the composition of saproxylic beetle assemblages in nine clear-cut, mature managed and old-growth spruce-domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(69 citation statements)
references
References 55 publications
3
63
3
Order By: Relevance
“…Other bird studies indicate that local stand variables are important predictors of bird species richness, although some also highlight the importance of the broader landscape context [50,73]. As such, our results do not contradict previous findings, highlighting the importance of the landscape context for explaining local biodiversity patterns (e.g., [14,74]), because we did not specifically evaluate additional effects of the landscape context after accounting for local-scale conditions. Additionally, although 50 m performed better, it is not necessarily the optimal radius, and more research would be needed to determine the best radius.…”
Section: Do the Models Perform Better When The Explanatory Variables contrasting
confidence: 47%
“…Other bird studies indicate that local stand variables are important predictors of bird species richness, although some also highlight the importance of the broader landscape context [50,73]. As such, our results do not contradict previous findings, highlighting the importance of the landscape context for explaining local biodiversity patterns (e.g., [14,74]), because we did not specifically evaluate additional effects of the landscape context after accounting for local-scale conditions. Additionally, although 50 m performed better, it is not necessarily the optimal radius, and more research would be needed to determine the best radius.…”
Section: Do the Models Perform Better When The Explanatory Variables contrasting
confidence: 47%
“…While the volume of CWD appeared in the best-Wt models for species richness and Rhimphoctona spp., it was not a signiWcant predictor. A similar lack of dependence on small-scale variation in substrate availability has commonly been found in studies examining the eVects of landscape variables on saproxylic beetles (Siitonen 1994;Økland et al 1996;Gibb et al 2006). This lack of relationship between the abundance of their hosts and the volume of CWD in close proximity suggests that parasitoids would not Wnd prey more easily by searching in areas with locally higher volumes of CWD.…”
Section: Evects Of Cwd Volume and Host Abundancessupporting
confidence: 69%
“…Previous studies have tested the relationship between features of forestry-dominated landscapes and assemblages of saproxylic beetles (Økland et al 1996;Gibb et al 2006), but little is known about how host and landscape responses interact to aVect their parasitoids. Species belonging to higher trophic levels are particularly vulnerable to changes in landscape structure and composition, as a result of their reliance on intact trophic chains (Roland and Taylor 1997;Kruess and Tscharntke 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Although we caught a greater number of beetles in our traps, we had lower species richness than these other studies on subcortical insects. Possible reasons include: 1) inclusion of latesuccessional beetle taxa (e.g., Colydiidae, Elateridae, Passalidae, and Stapylinidae) by previous researchers in their analyses in contrast to inclusion of only earlysuccessional taxa in our study (Savely 1939;Gibb et al 2005); 2) the use of window-traps attached directly to the trees by previous researchers in contrast to baited Lindgren funnel traps hung from poles in our study (e.g., SverdrupThygeson and Birkemoe (2008) found that window traps hung directly on aspen trees caught more beetles associated with aspen than traps hanging freely); and 3) some of the highly specific semiochemical baits that we used attracted large numbers of target species, but captured far fewer taxa than did unbaited traps or more generically baited traps. The subcortical insect guild that we have characterized likely originated primarily from jack pine (P. banksiana) [e.g., I. grandicollis, I. perroti, I. pini, Pityogenes plagiatus plagiatus (LeConte) (all Scolytidae) and M. s. scutellatus (Cerambycidae)], with identifiable components from L. laricina, Picea glauca, P. resinosa, and P. strobus.…”
Section: Discussionmentioning
confidence: 99%